Cyclic fatigue resistance of three Nickel-Titanium rotary files in single curvature canals: An in-vitro analysis - Kiranmurthy Dhananjaya; Amitu Singh; Nilotpol Kashyap; Shreya Rani; Soni Patel; Nishi Singh (Mashhad University of Medical Sciences, 2023)
Objective: This study aimed to evaluate the cyclic fatigue resistance (CFR) of three different heat-treated nickel-titanium (NiTi) files in rotary motion utilizing a cyclic fatigue testing device.Methods: Three NiTi rotary systems, Hero Gold, NeoEndo Flex, and T-Pro were used in this study. Ten files from each system (4% taper, #25 size, 21mm length) were tested for CFR. The test was conducted in an artificial canal in a customized cyclic fatigue device. The canal system is comprised of a 60° angle of curvature located 8 mm from the orifice. All files were rotated until fracture at the rotation per minute (RPM) and torque settings according to the manufacturer's recommendation. The time to fracture (TTF) was recorded in seconds for each instrument and then multiplied by (RPM/60) to obtain the number of cycles to fracture (NCF). The fracture length of each instrument fragment was recorded. Data were analyzed by one-way ANOVA and Tukey test and P-value <0.05 was considered statistically‌‌‌‌‌‌‌‌‌‌‌ significant.Results: The NiTi rotary systems demonstrated significantly different TTF values (P=0.001). Hero Gold exhibited a significantly higher TTF (114.13±4.21), followed by NeoEndo Flex (65.24±2.20) and T-Pro (40.50±3.45). The difference in TTF was also significant between NeoEndo Flex and T-Pro groups (P<0.05). There was no statistically significant difference in the length of the fractured fragments between the three groups (P=0.08).Conclusion: The Hero Gold file system demonstrated significantly superior CFR compared to the NeoEndo Flex and T-Pro systems, possibly due to differences in manufacturing processes for different file systems.